Perceived Authenticity In Narrative-Based Career Planning Education: An Experimental Study Among Vocational Students At Weifang Vocational College, China - Zhenzhen, Yang; Corbeta-Gomez, Serena; E. Borines, Marissa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates how narrative framing affects students’ perceived authenticity and learning responses in career planning education. A total of 189 students from Weifang Vocational College (Mage = 18.6, 52.4% female) were randomly assigned to one of three experimental conditions: original (graduate self-narrated), reenacted (actor-performed), or reconstructed (scripted voiceover). All groups received the same career story content, differing only in delivery. Participants completed standardized scales measuring perceived authenticity (trustworthiness, typicality, vividness, control), emotional involvement, situational vocational interest, and career misconceptions. Structural equation modeling (SEM) with MLR estimation and bootstrapping (5,000 resamples) was employed to test direct and mediated effects. Results indicated that narrative framing significantly influenced perceived authenticity (F = 11.84, p < 0.001), which in turn fully mediated effects on outcomes. Perceived authenticity predicted emotional involvement (β = 0.41, p < 0.001), vocational interest (β = 0.36, p = 0.002), and career misconceptions (β = 0.23, p = 0.017). Students in the original framing group reported 23.7% higher authenticity ratings and 19.5% greater emotional engagement than those in the reconstructed group. Direct effects of framing on outcomes were non-significant, underscoring the mediating role of authenticity perception. These findings offer new empirical support for designing perception-driven narrative interventions in career education and contribute to the theoretical refinement of authentic learning in vocational contexts.